Teacher Readiness in Preparing Learning Media - Hermawan, Hermawan; Surya, Julia; Ponijan, Ponijan (CV. Rayyan Dwi Bharata, 2024)
This study discusses the readiness of teachers in preparing instructional media and examines the creativity of teachers in creating or preparing instructional media in the classroom. Teacher readiness in utilizing instructional media involves more than just technological skills. It encompasses a profound understanding of students' needs, the ability to design relevant learning materials, and creativity in presenting information to make it easily understood by students. The research method applied in this study is a systematic literature review (SLR) to collect and analyze relevant articles. The results of this study indicate that teachers need to be ready for the digital era with digital literacy, technological experience, and a progressive attitude. The process of integrating instructional media faces obstacles such as a lack of training, uncertainty in choosing platforms, and differences in the availability of technology in various educational environments